Biomarkers in Psychiatry (Current Topics in Behavioral Neurosciences,, 2018)
This volume addresses one of the Holy Grails in Psychiatry, namely the evidence for and potential to adopt 'Biomarkers' for prevention, diagnosis, and treatment responses in mental health conditions. It meshes together state of the art research from international renowned pre-clinical and clinical scientists to illustrate how the fields of anxiety disorders, depression, psychotic disorders, and autism spectrum disorder have advanced in recent years.